(3Gdbhd GdLGeY aj eYQaI CSQGQ GdWHGjY heG ajgG ef GdefGaY Ydi GdJeGe hGdceGds ((3Shjai Hf CMeO GdYOhi s)
(3ChdgG (B:s
(3hHYO agPg QSGdI ai GdWHGFY GdCQHY GdehYhO HPcQgG ai Yde GdejRGf hEbGeI GdCLSGO HCfaSgG ef ZjQ CcSjQ s
(3BNQgG (B:s
(3adeG WGdHhgG HdZhG efgG gPg GdefRdI hbO JeJ gPg GdQSGdI GdLGeYI GddWHGFY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdbGgQI (B(26189) s
Keywords: (3GdcjejGA h GdWHjYjGJs